Asymmetric α-Allylation of α-Branched Aldehydes with Allyl Alcohols by Synergistic Catalysis Using an Achiral Palladium Complex and a Chiral Primary Amino Acid - Yoshida, Masanori; Masaki, Erika; Terumine, Tatsuaki; Hara, Shoji (Synthesis, 2014)
Highly enantioselective direct α-allylation of α-branched aldehydes with simple allyl alcohols was achieved by the combined use of an achiral transition-metal catalysis with a palladium complex and a chiral organocatalysis with a readily obtainable primary α-amino acid. Various α-allylated aldehydes possessing a stereocontrolled quaternary carbon stereogenic center were synthesized in high yields with high enantioselectivity.
Keywords: aldehydes; allylation; amino acids; asymmetric catalysis; palladium